If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4w + 2(w + -3) = 6 Reorder the terms: -4w + 2(-3 + w) = 6 -4w + (-3 * 2 + w * 2) = 6 -4w + (-6 + 2w) = 6 Reorder the terms: -6 + -4w + 2w = 6 Combine like terms: -4w + 2w = -2w -6 + -2w = 6 Solving -6 + -2w = 6 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2w = 6 + 6 Combine like terms: -6 + 6 = 0 0 + -2w = 6 + 6 -2w = 6 + 6 Combine like terms: 6 + 6 = 12 -2w = 12 Divide each side by '-2'. w = -6 Simplifying w = -6
| (x+15)+110=180 | | 5b+11=56-46 | | 8X-15X-30X-51X=53X+172 | | -7W-4w-1-9w= | | -11=-7v+4(v+4) | | -1(18z-11)=15 | | 8(w-4)=-9w-49 | | 176=-16t^2+114t+6 | | 400x+.04=250x+.18 | | x+23+105=180 | | S/=p | | -2x+(5x-1)=x-1 | | 3x^2+10-144=0 | | -4(3n-1)=20 | | n/8-3=-9 | | t+9T+T+T= | | 20=4-(y+7) | | 3x^2+67x-146=0 | | 6-10c-1=4-4c | | -12=4u+4 | | 2(v+1)=3v+23 | | 3(x+5)+6=-6 | | 1/3x^2-10x | | -2a+7=-23 | | 3(y+4)-2y=2(y+1) | | (2x+4)9=(3x-30)9 | | 2(v+1)=3u+23 | | x=3x+6x-9 | | x^3-6x^2-20x+120=0 | | 4t+3m=1529 | | log^3=1 | | -2-5b+8b=-8(-3-6b)-5(8+6b) |